Tracing teachers' transformation of knowledge in social media. (January 2020) - van Bommel, Jorryt; Randahl, Ann-Christin; Liljekvist, Yvonne; Ruthven, Kenneth
Abstract: Social media represent an increasingly important vehicle for informal professional development amongst teachers, and provide an illuminating means of tracing their collective knowledge building. The study reported here examines six large Facebook groups, created by and for teachers in Sweden, to exchange information about the teaching of mathematics and Swedish. Analysis establishes that professional knowledge was made available in 86% of discussion threads, most commonly relating to Shulman's categories of Knowledge of Learners, Curricular Knowledge, and Pedagogical Content Knowledge. Participants acknowledged opportunities for professional learning in 88% of such threads, and showed new understanding in 11%, particularly in longer threads. Highlights: Social media groups are increasingly important as sites for informal teacher development. Collective knowledge building is illuminated by analysis of threads. 86% of analysed threads offer opportunities for professional learning. 11% of analysed threads provide evidence of participants showing new understanding. Learning relates mostly to Shulman categories of Knowledge of Learners, Curricular Knowledge, Pedagogical Content Knowledge.